Bentuk Pertunjukan Tari Jaran Kepang di Paguyuban Langen Turonggo Jati Desa Muncar Kabupaten Semarang - Khamdani, Muhammad; Paranti, Lesa (JPKS (Jurnal Pendidikan dan Kajian Seni), 2024)
Jaran Kepang Langen Turonggo Jati communities is one of the Jaran Kepang communities located in Muncar Village, Susukan District, Semarang Regency. This study aims to analyze and describe the form of Jaran Kepang dance performances in the Langen Turonggo Jati Jaran Kepang Society of Semarang Regency. The method used by researchers is a qualitative research method using a phenomenological research approach. The data collection techniques used include observation, interview and documentation methods. The data validity technique used uses triangulation by utilizing data sources and matching data with facts found in the field. The results showed that the youth version of the Jaran Kepang dance performance form in Langen Turonggo Jati communities consists of opening, core, and closing. The elements of the performance include theme, movement, accompaniment, actors, makeup and clothing, performance venue, property, and also the audience. The dance is themed as a warrior dance with a combination of pure and meaningful movements using gamelan musical accompaniment. This dance is performed by 8-10 players wearing beskapan costumes and using gagahan makeup. This dance uses the mandatory property of Jaran Kepang. This dance is usually performed in an open field.